Shear wave elastography findings of de Quervain tenosynovitis. Issue 95 (October 2017) - Turkay, Rustu; Inci, Ercan; Aydeniz, Banu; Vural, Meltem
Abstract: Objective: Our aim was to evaluate the feasibility of using shear wave elastography (SWE) to assess first extensor compartment tendons rigidity and its alterations with tenosynovitis. Materials and methods: We performed B-mode ultrasound and SWE to total number of 80 participants. All participants were evaluated clinically to call the diagnosis of de Quervain tenosynovitis or to rule out the diagnosis. We composed 2 groups. Group 1 included 40 healthy volunteers (33 females and 7 male participants with ages ranging from 24 to 60 years, median age was 37.5 years) and group 2 had 40 de Quervain patients (32 females and 8 male patients with ages ranging from 25 to 51 years, median age was 34 years). SWE measurements were repeated 3 times and arithmetic average was used for the final SWE value. Results: The median SWE value of healthy group (group 1) was 72 kPa and the de Quervain patient group (group 2) was 29 kPa. Two groups demonstrated statistically significant difference (p < 0.001). The ROC curve analysis was performed and the SWE value of 40.5kPA was calculated as a cut-off value for the diagnosis of de Quervain tenosynovitis with 95% specificity and 85% sensitivity. Conclusion: SWE modality can provide useful data regarding de Quervain tenosynovitis.